+0  
 
+1
161
2
avatar+809 

If \(t(x) = 3-g(x)\) and \(g(x)=\sqrt{x}\), then what is \(t(g(16))\)?

 Aug 27, 2018

Best Answer 

 #1
avatar+7352 
+3

g(x)  =  √x

                       Plug in  16  for  x .

g(16)  =  √16

 

g(16)  =  4

 

And...

 

t(x)  =  3 - g(x)

                                          Since  g(x)  =  √x  , we can substitute  √x  in for  g(x) .

t(x)  =  3 - √x

                                          Plug in  g(16)  for  x .

t(g(16))  =  3 - √[ g(16) ]

                                          Since  g(16)  =  4 , we can substitute  4  in for  g(16) .               

t(g(16))  =  3 - √[ 4 ]

 

t(g(16))  =  3 - 2

 

t(g(16))  =  1

 

Also...

 

t(g(16))  =  3 - g( g(16) )  =  3 - g( 4 )  =  3 - 2  =  1

 Aug 27, 2018
edited by hectictar  Aug 27, 2018
 #1
avatar+7352 
+3
Best Answer

g(x)  =  √x

                       Plug in  16  for  x .

g(16)  =  √16

 

g(16)  =  4

 

And...

 

t(x)  =  3 - g(x)

                                          Since  g(x)  =  √x  , we can substitute  √x  in for  g(x) .

t(x)  =  3 - √x

                                          Plug in  g(16)  for  x .

t(g(16))  =  3 - √[ g(16) ]

                                          Since  g(16)  =  4 , we can substitute  4  in for  g(16) .               

t(g(16))  =  3 - √[ 4 ]

 

t(g(16))  =  3 - 2

 

t(g(16))  =  1

 

Also...

 

t(g(16))  =  3 - g( g(16) )  =  3 - g( 4 )  =  3 - 2  =  1

hectictar Aug 27, 2018
edited by hectictar  Aug 27, 2018
 #2
avatar+809 
+4

Thank you, hectictar! Nice solution!

mathtoo  Aug 27, 2018

25 Online Users

avatar
avatar
avatar
avatar